Caracterização do perfil assistencial e clínico de pacientes em pulsoterapia de um hospital universitário - (:unkn) unknown (EEM - Escola de Enfermagem de Manaus, 2025)
Introduction: Pulse therapy uses high doses of intravenous corticosteroids, requiring nursing assistance due to possible adverse reactions; however, failures in staffing, training, overload, and interpersonal relationships compromise the quality of care. Objective: To characterize the clinical and care profile of adult patients treated in a pulse therapy unit at a university hospital. Method: Descriptive, cross-sectional study with a quantitative approach, to be conducted with patients receiving treatment in the pulse therapy department at a university hospital in Manaus/AM. Result: The majority of patients in pulse therapy were women aged 41 to 60 years, residing in Manaus, with multiple sclerosis and a predominance of minimal care. Twenty-two nursing diagnoses were identified based on "Nursing Diagnoses. Definitions and Classification 2024-2026" using the nursing history instrument based on the Theory of Basic Needs. Conclusion: The study emphasized the complexity of care in pulse therapy and the importance of the Fugulin Scale and the assessment of basic human needs to guide individualized, safe, and humane interventions.
Keywords: Pulsoterapia; Cuidados de enfermagem; Doenças autoimunes; Dimensionamento de pessoal; Diagnósticos de enfermagem; CIENCIAS DA SAUDE: ENFERMAGEM